Diagnostic pitfall in antenatal manifestations of CPT II deficiency. Issue 2 (5th May 2015) - Boemer, F.; Deberg, M.; Schoos, R.; Caberg, J.‐H.; Gaillez, S.; Dugauquier, C.; Delbecque, K.; François, A.; Maton, P.; Demonceau, N.; Senterre, G.; Ferdinandusse, S.; et al.
Abstract : Carnitine palmitoyltransferase II (CPT2) deficiency is a rare inborn error of mitochondrial fatty acid metabolism associated with various phenotypes. Whereas most patients present with postnatal signs of energetic failure affecting muscle and liver, a small subset of patients presents antenatal malformations including brain dysgenesis and neuronal migration defects. Here, we report recurrence of severe cerebral dysgenesis with Dandy–Walker malformation in three successive pregnancies and review previously reported antenatal cases. Interestingly, we also report that acylcarnitines profile, tested retrospectively on the amniotic fluid of last pregnancy, was not sensitive enough to allow reliable prenatal diagnosis of CPT2 deficiency. Finally, because fetuses affected by severe cerebral malformations are frequently aborted, CPT2 deficiency may be underestimated and fatty acid oxidation disorders should be considered when faced with a fetus with Dandy–Walker anomaly or another brain dysgenesis.